Pregnancy/abortion induced intracerebral hemorrhage during the first trimester in a young female (Indian Journal of Case Reports, 2021)
Intracranial hemorrhage is a relatively infrequent but devastating complication of pregnancy. Pregnancy-associated intracranial hemorrhage is a rare but severe complication. Mostly, the incidence of ICH occurs during the third trimester of pregnancy. In our case, an 18-year-old girl who had Glasgow coma scale score of 5/15, admitted to the hospital with no movement of left-sided upper and lower limb with right-sided facial deviation. Computed tomography (CT) brain revealed that the patient has right-sided temporoparietal bleed. The patient underwent right-sided hemicraniotomy. An obstetrical ultrasound report suggested a gestation of 12 weeks. The history of the patient highlighted an attempt of unsupervised termination of pregnancy using off-the-counter pills. In this case, we reported the rare intracerebral hemorrhage during the first trimester. Pregnancy has not been shown to be a direct cause of intracerebral bleed; hence, this case draws attention to the hazards of unsupervised termination of pregnancy.